The mechanical properties and thermal stability of ultrathin germanium nanowires. Issue 107 (7th November 2016) - Yang, Po-Yu; Ju, Shin-Pon; Lai, Zhu-Min; Hsieh, Jin-Yuan; Lin, Jenn-Sen
Abstract : The mechanical properties of ultrathin germanium nanowires are investigated: the mechanical properties of the nanowires are severely reduced when temperature increases. Abstract : The most stable structures of four ultrathin germanium nanowires (GeNWs) were predicted by a simulated annealing basin-hopping method (SABH) with a Stillinger–Weber (SW) potential, including helix, pentagon, hexagon and 7-1 nanowires. The size and temperature dependence of the tensile behavior and mechanical properties are investigated to approach a real environment. The ultimate tensile strength, strain at failure and Young's modulus are evaluated. All the mechanical properties of nanowires are severely reduced when temperature increases from 20 K to 180 K, but become less severe at high temperature. At room temperature (300 K), the yielding stress and Young's modulus of all nanowires are higher than bulk, and the pentagonal NW exhibits the best mechanical properties among these three GeNWs. This study also demonstrates that the mechanical properties are not proportional to the size or radius of ultrathin GeNWs, a phenomenon different from that in the bulk. In addition, the phonon density of states and thermal stability of GeNWs are also discussed in this study.